The identity of Clematis zhejiangensis (Ranunculaceae) from China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2018)
We demonstrate that Clematis zhejiangensis (Ranunculaceae) is conspecific with C. uncinata, a species widespread in subtropical regions in China and the neighboring countries. We therefore reduce C. zhejiangensis to the synonymy of C. uncinata. The varietal division of C. uncinata is briefly reviewed, and the type information of C. leiocarpa, which has been reduced to the synonymy of C. uncinata var. uncinata or C. uncinata var. coriacea, is also discussed. Furthermore, the likelihood of confusion between C. zhejiangensis and C. chekiangensis is mentioned.